A nitrogen-doped porous silicon-carbon negative electrode material and its preparation method and application

By doping nitrogen into a porous carbon matrix and performing chemical vapor deposition, a nitrogen-doped porous silicon-carbon anode material was prepared, which solved the problems of volume expansion and poor conductivity of silicon-based anode materials during cycling, and achieved high capacity and low expansion. performance improvements in efficiency and long cycle life.

CN119038558BActive Publication Date: 2025-01-24LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411533624.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-24
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The existing silicon-based anode materials have problems of volume expansion and poor conductivity during the cycle, resulting in damage to the electrode structure, rapid decline in capacity, and cumbersome preparation steps and high cost, which limits its commercial application.

Method used

By performing nitrogen doping of porous carbon in the protective atmosphere, a nitrogen-containing carbon matrix with C-N bonds is formed, and the chemical gas deposition of nitrogen sources and silicon source mixed gas is deposited. Silicon particles and nitrogen doped silicon particles are prepared to prepare nitrogen doped porous silicon carbon negative materials.

Benefits of technology

It improves the effective deposition of silicon and the utilization rate of silicon source gases, improves the performance of nitrogen doped porous silicon carbon negative materials, and enables it to have high capacity, low expansion rate, high -end circle Kuron efficiency, long cycle life and high magnification performance Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119038558B_ABST
    Figure CN119038558B_ABST
Patent Text Reader

Abstract

This invention relates to a nitrogen-doped porous silicon-carbon anode material, its preparation method, and its application. The preparation method includes: placing porous carbon in a reactor under a protective atmosphere and heating it, while introducing a nitrogen source gas for heat preservation, to obtain a nitrogen-containing porous carbon matrix; wherein the carbon element in the nitrogen-containing porous carbon matrix forms C-N bonds with the nitrogen element; placing the nitrogen-containing porous carbon matrix in a reactor and heating it, while introducing a mixed gas of nitrogen source gas and silicon source gas, during the heat preservation process, the C-N bonds induce silicon source gas deposition, resulting in the uniform deposition of nano-silicon particles and nitrogen-doped silicon particles in the pores of the nitrogen-containing porous carbon matrix; after cooling to room temperature, and after dispersion, sieving, and demagnetization, the nitrogen-doped porous silicon-carbon anode material is obtained; using the nitrogen-doped porous silicon-carbon anode material of this invention in lithium-ion batteries can improve the battery's specific capacity, first-cycle coulombic efficiency, rate performance, and cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a nitrogen-doped porous silicon-carbon negative electrode material and a preparation method and application thereof. Background Art

[0002] The theoretical gram capacity of graphite anode is low, while silicon-based materials have the advantages of abundant reserves, environmental friendliness, and low price, and are considered one of the most promising anode materials. However, silicon-based materials have huge volume expansion during the cycle process, which will cause the silicon particles to break, leading to electrode pulverization, damage to the electrode structure, and rapid capacity decay. In addition, silicon-based materials also have problems such as low conductivity, which limits the commercial application of silicon-based anodes.

[0003] In order to solve the problems of silicon volume expansion and poor conductivity, chemical vapor deposition is often used in the prior art to deposit silicon in the pores of a porous carbon matrix, and then post-treatment such as surface coating is performed to obtain a silicon-carbon composite material; however, this method still has some problems. Directly depositing silicon in a porous carbon matrix is ​​not conducive to the effective deposition of silicon particles and the effective utilization of silicon source gas; post-treatment methods such as carbon coating, graphene composite or carbon nanotube composite are cumbersome and costly, which is not conducive to the large-scale industrial production of silicon-based negative electrode materials.

[0004] For example, the Chinese invention patent with publication number CN110600719A (published on December 20, 2019) discloses a porous silicon-carbon lithium-ion battery negative electrode material with high rate performance and its preparation method. This patent obtains a porous carbon precursor by coprecipitation reaction of a protein solution and a soluble transition metal salt, and then reduces it at high temperature to obtain a nitrogen-doped porous silicon-carbon negative electrode material, using the native porous environment of porous carbon to provide space for volume expansion during lithium insertion. Although this invention patent achieves nitrogen doping of porous carbon, it does not regulate the content and distribution sites of nitrogen elements, and cannot guarantee the uniformity of the subsequent induced nano-silicon deposition, and the preparation steps are cumbersome.

[0005] The Chinese invention patent with publication number CN114051663A (publication date February 15, 2022) discloses a negative electrode material and its preparation method, an electrochemical device and an electronic device. This patent is to obtain nitrogen-doped porous carbon by subjecting antibiotic bacterial residue to high-temperature carbonization treatment with metal salts and pickling treatment, and then use silane gas to vapor-deposit the nitrogen-doped porous carbon and then mix it with a carbon source for carbon composite treatment to finally obtain the negative electrode material. This method deposits silicon material on the pore wall of nitrogen-doped porous carbon, and uses nitrogen-doped porous carbon as the supporting skeleton of the negative electrode material, and its internal pores can alleviate a certain volume expansion; this invention mainly controls the ratio of the thickness of the silicon-containing material layer to the pore size of the nitrogen-doped porous carbon, and the ratio of the thickness of the silicon-containing material layer to the thickness of the carbon layer, so as to avoid the expansion of the silicon-containing material layer from destroying the pore structure and carbon layer of the nitrogen-doped porous carbon. However, since the negative electrode material of this invention patent is obtained by nitrogen-doped porous carbon through high-temperature carbonization treatment of antibiotic bacterial residue with metal salts and acid washing, the uniformity of nitrogen doping in the porous carbon is relatively poor. Therefore, the uniformity of the distribution of nano-silicon deposition cannot be guaranteed during the subsequent silicon deposition.

[0006] The Chinese invention patent application with publication number CN116799178A (publication date September 22, 2023) discloses a silicon-carbon negative electrode material and a preparation method thereof, and a lithium-ion battery, by pre-forming a SiN with a suitable composition on the surface of a porous carbon substrate. x A thin layer is formed, followed by silicon deposition; finally, a high-temperature carbon coating process is performed to obtain a silicon-carbon negative electrode material. x The thin layer can prevent the deposited silicon from reacting with the carbon substrate during the subsequent high-temperature carbonization process. At the same time, it will not block the pore structure of the porous silicon. It can fully play the role of the porous structure in buffering the expansion of silicon and can continue to combine with lithium ions. However, it is not very helpful for the uniformity of the distribution of the subsequent deposited silicon and the effect is limited. Summary of the invention

[0007] The purpose of the present invention is to address the defects of the prior art and propose a nitrogen-doped porous silicon-carbon negative electrode material and its preparation method and application. By nitrogen-doping porous carbon under a protective atmosphere, a nitrogen-containing porous carbon matrix with CN bonds is obtained, and then nano-silicon particles and nitrogen-doped silicon particles are deposited in the pores of the nitrogen-containing porous carbon matrix by chemical vapor deposition of a nitrogen source and silicon source mixed gas to prepare a nitrogen-doped porous silicon-carbon negative electrode material. The nitrogen-doped porous silicon-carbon negative electrode material is beneficial to improving the effective deposition of silicon and the utilization rate of the silicon source gas during the preparation of the nitrogen-containing porous carbon matrix due to the presence of CN bonds, thereby improving the performance of the nitrogen-doped porous silicon-carbon negative electrode material, so that it has the characteristics of high capacity, low expansion rate, high first-cycle coulomb efficiency, long cycle life and high rate performance.

[0008] To achieve the above objectives, in a first aspect, an embodiment of the present invention provides a method for preparing a nitrogen-doped porous silicon-carbon negative electrode material, the preparation method comprising:

[0009] Step S1, placing porous carbon in a reaction furnace under a protective atmosphere, heating it to a first temperature, introducing a first nitrogen source gas, and cooling it to room temperature after a first insulation process to obtain a nitrogen-containing porous carbon matrix in which nitrogen is doped in the pores of the porous carbon; wherein the carbon element of the nitrogen-containing porous carbon matrix forms a CN bond with the nitrogen element; the mass percentage of the nitrogen element in the nitrogen-containing porous carbon matrix is ​​2% to 10% of the mass percentage of the nitrogen-containing porous carbon matrix.

[0010] Step S2, under a protective atmosphere, placing the nitrogen-containing porous carbon matrix in a reaction furnace, heating it to a second temperature, introducing a second nitrogen source gas and a silicon source gas, and undergoing a second heat preservation process, wherein the CN bond induces the deposition of the silicon source gas so that nano-silicon particles and nitrogen-doped silicon particles are uniformly deposited in the pores of the nitrogen-containing porous carbon matrix, and then cooling to room temperature, breaking up, screening and demagnetizing to obtain a nitrogen-doped porous silicon-carbon negative electrode material.

[0011] Preferably, the particle size Dv50 of the porous carbon is 5nm to 8nm; the pore size of the porous carbon is 1.5nm to 2nm; and the porosity of the porous carbon is 50% to 70%.

[0012] The mass ratio of the nano silicon particles to the nitrogen-doped silicon particles is 95%:5% to 90%:10%.

[0013] Preferably, the protective atmosphere is an argon atmosphere.

[0014] The first nitrogen source gas includes: one or more of ammonia and nitrogen oxides; the flow rate of the first nitrogen source gas is 12L / min to 16L / min.

[0015] The second nitrogen source gas includes: one or more of ammonia and nitrogen oxides; the flow rate of the second nitrogen source gas is 12L / min to 16L / min.

[0016] The silicon source gas includes one or more of monosilane, disilane, dichlorosilane, trichlorosilane, tetrachlorosilane and hexachlorodisilane.

[0017] The flow ratio of the silicon source gas to the second nitrogen source gas is between 3:1 and 8:1.

[0018] Preferably, the heating to the first temperature in step S1 includes: heating to 500° C. to 700° C. at a heating rate of 1° C. / min to 5° C. / min.

[0019] The first heat preservation process includes: heat preservation at 500° C. to 700° C. for 1 hour to 5 hours.

[0020] Preferably, the rotation speed of the reaction furnace in step S2 is 80 rpm to 100 rpm.

[0021] The heating to the second temperature includes: heating to 500° C. to 700° C. at a heating rate of 1° C. / min to 5° C. / min.

[0022] The second heat preservation process includes: heat preservation at 500° C. to 700° C. for 1 hour to 5 hours.

[0023] Preferably, the dispersing device is a disperser; the speed of the disperser is between 80 r / min and 1500 r / min, and the dispersing time is 0.5 hour to 2 hours.

[0024] The mesh number of the sieving is between 200 mesh and 500 mesh.

[0025] In the second aspect, an embodiment of the present invention provides a nitrogen-doped porous silicon-carbon negative electrode material prepared based on the preparation method described in the first aspect, wherein the nitrogen-doped porous silicon-carbon negative electrode material includes a nitrogen-containing porous carbon matrix, and nano-silicon particles and nitrogen-doped silicon particles deposited in the pores of the nitrogen-containing porous carbon matrix.

[0026] Preferably, the mass ratio of the nano-silicon particles to the nitrogen-doped silicon particles is 95%:5% to 90%:10%.

[0027] The mass of the nano silicon particles accounts for 40% to 52% of the total mass of the nitrogen-doped porous silicon-carbon negative electrode material.

[0028] The particle size range Dv50 of the nitrogen-doped porous silicon-carbon negative electrode material is 5nm to 8nm.

[0029] In a third aspect, an embodiment of the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the nitrogen-doped porous silicon-carbon negative electrode material described in the first aspect.

[0030] In a fourth aspect, an embodiment of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode plate described in the third aspect above; the lithium-ion battery comprises a liquid lithium-ion battery, a semi-solid lithium-ion battery or an all-solid lithium-ion battery.

[0031] A method for preparing a nitrogen-doped porous silicon-carbon negative electrode material is provided in an embodiment of the present invention. The method comprises the following steps: nitrogen-doping porous carbon under a protective atmosphere to obtain a nitrogen-containing porous carbon matrix having a CN bond, and then depositing nano-silicon particles and nitrogen-doped silicon particles in the pores of the nitrogen-containing porous carbon matrix through chemical vapor deposition of a mixed gas of a nitrogen source and a silicon source to obtain a nitrogen-doped porous silicon-carbon negative electrode material.

[0032] The present invention uses vapor deposition to dope nitrogen in the pores of porous carbon, so that nitrogen can be effectively deposited inside the pore structure and evenly distributed at the same time, thereby ensuring the uniformity of doped nitrogen, and further forming uniform CN bonds. In the co-deposition process of nitrogen source gas and silicon source gas, efficient and uniform deposition can be achieved under the induction of CN bonds; this is because the CN bonds can generate intermediates with higher reaction activity through reaction with the silicon source, thereby promoting the deposition of silicon; the introduction of the CN bonds can reduce the energy barrier of the reaction, adjust the temperature and pressure conditions during the deposition process, thereby reducing the deposition temperature, and optimizing the deposition rate and deposition quality; the CN bonds can inhibit the occurrence of side reactions, so that more silicon source gas can participate in the target reaction, and improve its utilization rate; the CN bonds can improve the adsorption capacity of silicon atoms on the surface of the substrate, so that the silicon atoms can be more stably attached to the substrate, thereby promoting their aggregation and growth.

[0033] The nitrogen-doped porous silicon-carbon negative electrode material obtained by the above-mentioned preparation method in the embodiment of the present invention is conducive to improving the effective deposition of silicon and the utilization rate of silicon source gas due to the presence of CN bonds in the process of preparing the nitrogen-containing porous carbon matrix, thereby improving the performance of the nitrogen-doped porous silicon-carbon negative electrode material, so that it has the characteristics of high capacity, low expansion rate, high first-cycle coulomb efficiency, long cycle life and high rate performance. The nitrogen-doped porous silicon-carbon negative electrode material provided by the embodiment of the present invention is applied to lithium-ion batteries, which can improve the charging specific capacity, first-cycle coulomb efficiency, rate performance and cycle life of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Flow chart of the preparation method of nitrogen-doped porous silicon-carbon negative electrode material provided in an embodiment of the present invention.

[0035] Figure 2 The charge and discharge curve diagram of the assembled battery of Example 1 provided in the embodiment of the present invention.

[0036] Figure 3 A cycle curve diagram of the assembled battery of Example 1 after 100 cycles provided in the embodiments of the present invention. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0039] The present invention provides a method for preparing a nitrogen-doped porous silicon-carbon negative electrode material. Figure 1 As shown, the specific steps include the following steps.

[0040] Step S1, placing porous carbon in a reaction furnace under a protective atmosphere, heating it to a first temperature, introducing a first nitrogen source gas, and cooling it to room temperature after a first insulation process to obtain a nitrogen-containing porous carbon matrix in which nitrogen is doped in the pores of the porous carbon.

[0041] Among them, the carbon element of the nitrogen-containing porous carbon matrix forms a CN bond with the nitrogen element. The CN bond can improve the adsorption ability of silicon atoms on the substrate surface, allowing silicon atoms to attach to the substrate more stably, thereby promoting their aggregation and growth. The CN bond can promote the orderly growth of silicon crystals, improve the crystal structure, and reduce defects that may occur during the deposition process. A more ordered crystal structure helps the aggregation and growth of silicon atoms, thereby forming a more uniform and dense crystal structure.

[0042] The mass percentage of nitrogen in the nitrogen-containing porous carbon matrix to the mass percentage of the nitrogen-containing porous carbon matrix is ​​2% to 10%, which can be any value within the range of 2% to 10%, for example: 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. The mass percentage of nitrogen in the nitrogen-containing porous carbon matrix to the mass percentage of the nitrogen-containing porous carbon matrix is ​​preferably 4% to 6%.

[0043] Specifically, the protective atmosphere is an argon atmosphere.

[0044] The particle size Dv50 of the porous carbon is 5nm to 8nm; the pore size of the porous carbon is 1.5nm to 2nm; and the porosity of the porous carbon is 50% to 70%.

[0045] The first nitrogen source gas includes: one or more of ammonia and nitrogen oxides; wherein the nitrogen oxides include: one or more of nitrous oxide (N2O), nitric oxide (NO), nitrogen dioxide (NO2), nitrogen trioxide (N2O3), nitrogen tetroxide (N2O4) and nitrogen pentoxide (N2O5); the flow rate of the first nitrogen source gas is 12L / min to 16L / min.

[0046] In this step, heating to the first temperature specifically includes heating to 500° C. to 700° C. at a heating rate of 1° C. / min to 5° C. / min.

[0047] The first heat preservation process includes: heat preservation at 500° C. to 700° C. for 1 hour to 5 hours.

[0048] The temperature of the first insulation in this step can be any temperature value in the range of 500℃ to 700℃, for example: 500℃, 510℃, 520℃, 530℃, 540℃, 550℃, 560℃, 570℃, 580℃, 590℃, 600℃, 610℃, 620℃, 630℃, 640℃, 650℃, 660℃, 670℃, 680℃, 690℃, 700℃, etc., but is not limited to the listed temperature values, and other temperatures not listed within the temperature value range are also applicable.

[0049] The first insulation time in this step can be any value in the range of 1 hour to 5 hours, for example: 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] Step S2, under a protective atmosphere, placing the nitrogen-containing porous carbon matrix in a reaction furnace, heating it to a second temperature, introducing a second nitrogen source gas and a silicon source gas, and undergoing a second heat preservation process, the CN bond induces the deposition of the silicon source gas so that nano-silicon particles and nitrogen-doped silicon particles are uniformly deposited in the pores of the nitrogen-containing porous carbon matrix, and then cooling to room temperature, breaking up, screening and demagnetizing to obtain a nitrogen-doped porous silicon-carbon negative electrode material.

[0051] Among them, in the final nitrogen-doped porous silicon-carbon negative electrode material, the mass ratio of nano silicon particles and nitrogen-doped silicon particles (Si-N) is 95%:5% to 90%:10%.

[0052] The second nitrogen source gas includes: one or more of ammonia and nitrogen oxides; wherein the nitrogen oxides include: one or more of nitrous oxide (N2O), nitric oxide (NO), nitrogen dioxide (NO2), nitrogen trioxide (N2O3), nitrogen tetroxide (N2O4) and nitrogen pentoxide (N2O5); the flow rate of the second nitrogen source gas is 12L / min to 16L / min.

[0053] The silicon source gas includes one or more of monosilane, disilane, dichlorosilane, trichlorosilane, tetrachlorosilane, and hexachlorodisilane.

[0054] The volume flow ratio of the silicon source gas to the second nitrogen source gas is between 3:1 and 8:1, and can be any ratio within the above range, for example: 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, etc., but is not limited to the listed ratios, and other unlisted ratios within the ratio range are also applicable.

[0055] In this step, the rotation speed of the reaction furnace is 80 rpm to 100 rpm; generally, the pressure in the reaction furnace should be less than or equal to 10 kPa to ensure safety.

[0056] The heating to the second temperature specifically includes heating to 500° C. to 700° C. at a heating rate of 1° C. / min to 5° C. / min.

[0057] The second heat preservation process includes: heat preservation at 500° C. to 700° C. for 1 hour to 5 hours.

[0058] The temperature of the second insulation in this step can be any temperature value in the range of 500℃ to 700℃, for example: 500℃, 510℃, 520℃, 530℃, 540℃, 550℃, 560℃, 570℃, 580℃, 590℃, 600℃, 610℃, 620℃, 630℃, 640℃, 650℃, 660℃, 670℃, 680℃, 690℃, 700℃, etc., but is not limited to the listed temperature values, and other temperatures not listed within the temperature value range are also applicable.

[0059] The insulation time of the second insulation in this step can be any value in the range of 1 hour to 5 hours, for example: 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0060] The rotation speed of the reactor is 80 rpm to 100 rpm. The purpose of rotating the reactor is to make the reaction in the furnace more complete and improve the performance of the material during the preparation of nitrogen-doped porous silicon-carbon negative electrode materials.

[0061] The dispersing, screening and demagnetization in this step are all conventional known methods, wherein the dispersing equipment is a disperser; the speed of the disperser is between 80r / min and 1500r / min, the dispersing time is 0.5 hour to 2 hours, and the mesh size of the sieve is between 200 mesh and 500 mesh.

[0062] The preparation method of the present invention pre-dopes nitrogen into a porous carbon matrix, and then co-deposits a nitrogen source gas and a silicon source gas to first generate nano-silicon and nitrogen-doped silicon particles under the induction of CN bonds, thereby further improving the conductivity of the material.

[0063] The nitrogen-doped porous silicon-carbon negative electrode material prepared by the above-mentioned preparation method in the embodiment of the present invention includes a nitrogen-containing porous carbon matrix, and nano-silicon particles and nitrogen-doped silicon particles deposited in the pores of the nitrogen-containing porous carbon matrix.

[0064] Among them, the mass ratio of nano silicon particles and nitrogen-doped silicon particles is 95%:5% to 90%:10%.

[0065] The mass of the nano-silicon particles accounts for 40% to 52% of the total mass of the nitrogen-doped porous silicon-carbon negative electrode material.

[0066] The particle size range Dv50 of the nitrogen-doped porous silicon-carbon negative electrode material is 5nm to 8nm.

[0067] The nitrogen-doped porous silicon-carbon negative electrode material provided in the embodiment of the present invention can be used to prepare a negative electrode plate, and the negative electrode plate can be used to assemble a lithium-ion battery. Among them, the lithium-ion battery includes: the lithium-ion battery includes a liquid lithium-ion battery, a semi-solid lithium-ion battery or an all-solid lithium-ion battery. The capacity, first-cycle coulomb efficiency, rate performance and cycle life of the lithium-ion battery can be improved; the embodiment of the present invention assembles button batteries and performs cycle and rate tests on them. The button batteries tested have a high first-cycle charging specific capacity (greater than 1700mAh / g), a relatively high first-cycle coulomb efficiency, and a capacity retention rate of more than 85% after 100 stable cycles. This is because when preparing the nitrogen-doped porous silicon-carbon negative electrode material, the present invention uses gas phase deposition to dope nitrogen in the pores of the porous carbon, which can make the nitrogen effectively deposited inside the pore structure and evenly distributed at the same time, thereby ensuring the uniformity of the doped nitrogen, and then forming a uniform CN bond. In the co-deposition process of the nitrogen source gas and the silicon source gas, since the CN bond can generate an intermediate with higher reactivity (usually a silicon nitrogen compound, such as silazane or a silicon nitrogen group) through the reaction with the silicon source, the deposition of silicon is promoted, and the introduction of the CN bond can reduce the energy barrier of the reaction, adjust the temperature and pressure conditions during the deposition process, thereby reducing the deposition temperature, optimizing the deposition rate and deposition quality, and at the same time, the CN bond can inhibit the occurrence of side reactions, so that more silicon source gas participates in the target reaction, and improves the utilization rate of the silicon source gas. The CN bond can also improve the adsorption capacity of silicon atoms on the substrate surface, so that silicon atoms can be more stably attached to the substrate, thereby promoting its aggregation and growth, so the nitrogen source gas and the silicon source gas can be induced by the CN bond to achieve efficient and uniform deposition, thereby improving the performance of the nitrogen-doped porous silicon-carbon negative electrode material.

[0068] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the nitrogen-doped porous silicon-carbon negative electrode material of the present invention are respectively described below with multiple specific examples.

[0069] Example 1

[0070] This embodiment provides a preparation process of a nitrogen-doped porous silicon-carbon negative electrode material, and the specific process is as follows.

[0071] (1) Under argon atmosphere, 1 kg of porous carbon was placed in a reactor with a rotation speed of 100 r / min. The temperature was raised to 500°C at a heating rate of 5°C / min, and ammonia was introduced at a flow rate of 15 L / min. The temperature was kept warm for 2 hours. After the temperature was kept warm, the temperature was lowered to room temperature in the argon atmosphere to obtain a nitrogen-containing porous carbon matrix with nitrogen doped in the pores of the porous carbon. A nitrogen-oxygen-hydrogen analyzer (LECOONH836) was used to determine that the nitrogen element accounted for 5% of the mass of the nitrogen-containing porous carbon matrix.

[0072] (2) In an argon atmosphere, the nitrogen-containing porous carbon matrix is ​​placed in a reaction furnace, the speed of the reaction furnace is 100 rpm, the temperature is raised to 550°C at a heating rate of 5°C / min, and then a mixed gas of monosilane and ammonia (the volume flow ratio of monosilane and ammonia is 4:1) is introduced at a flow rate of 12 L / min, and the temperature is kept for 3 hours. During the reaction, the pressure in the furnace is kept ≤10 kPa. In this process, the CN bond induces the deposition of silicon source gas so that nano-silicon particles and nitrogen-doped silicon particles are uniformly deposited in the pores of the nitrogen-containing porous carbon matrix. After the insulation is completed, the temperature is lowered to room temperature in the argon atmosphere. After being dispersed, sieved and demagnetized, a nitrogen-doped porous silicon-carbon negative electrode material is obtained. The increment of nano-silicon particles and nitrogen-doped silicon particles accounts for 47wt% of the total mass of the nitrogen-doped porous silicon-carbon negative electrode material, wherein the increment of nano-silicon particles and nitrogen-doped silicon particles refers to the difference between the mass of the nitrogen-doped porous silicon-carbon negative electrode material obtained in step (2) and the mass of the nitrogen-containing porous carbon matrix obtained in step (1).

[0073] Example 2

[0074] The preparation process of the nitrogen-doped porous silicon-carbon negative electrode material in this embodiment is basically the same as that in Example 1, with the only difference being that the holding time in step (1) is 1 hour, the doped nitrogen element accounts for 3% of the mass of the nitrogen-containing porous carbon matrix, and the final increment of nano-silicon particles and nitrogen-doped silicon particles accounts for 45wt% of the total mass of the nitrogen-doped porous silicon-carbon negative electrode material.

[0075] Example 3

[0076] The preparation process of the nitrogen-doped porous silicon-carbon negative electrode material in this embodiment is basically the same as that in Example 1, with the only difference being that the insulation time in step (1) is 4 hours, the doped nitrogen element accounts for 8% of the mass of the nitrogen-containing porous carbon matrix, and the final increment of nano-silicon particles and nitrogen-doped silicon particles accounts for 49wt% of the total mass of the nitrogen-doped porous silicon-carbon negative electrode material.

[0077] In order to better illustrate the effects of the embodiments of the present invention, comparative examples 1-2 are compared with the above embodiments 1-3.

[0078] Comparative Example 1

[0079] The preparation process of the negative electrode material in this comparative example is basically the same as that in Example 1, with the only difference being that the holding time in step (1) is only 0.5 h, the doped nitrogen element accounts for 0.5% of the mass of the nitrogen-containing porous carbon matrix, and the mass of the final nano-silicon particles and nitrogen-doped silicon particles accounts for 42 wt% of the total mass of the negative electrode material.

[0080] Since the heat preservation time in step (1) of this comparative example 1 is shorter, the content of nitrogen element doped in the nitrogen-containing porous carbon matrix is ​​less than that in Example 1. Therefore, after the subsequent deposition of step (2) which is the same as that in Example 1, the mass proportion of nano silicon particles and nitrogen-doped silicon particles in the negative electrode material of comparative example 1 is less than that in Example 1. This indicates that the CN bond formed between the carbon element and the nitrogen element in the nitrogen-containing porous carbon matrix in step (1) is beneficial to the subsequent deposition of silicon.

[0081] Comparative Example 2

[0082] This comparative example provides a negative electrode material preparation process, which is different from Example 1 in that the process of preparing the nitrogen-containing porous carbon matrix in step (1) is not performed, and the preparation process is basically the same as that in step (2) of Example 1, specifically: in an argon atmosphere, 1 kg of porous carbon is directly placed in a reactor, the speed of the reactor is 100 rpm, the temperature is raised to 550°C at a heating rate of 5°C / min, and then a mixed gas of monosilane and ammonia (the volume flow ratio of monosilane and ammonia is 4:1) is introduced at a flow rate of 12 L / min, and the temperature is kept for 3 hours. During the reaction, the pressure in the furnace is kept ≤10 kPa. After the temperature is kept, the pressure is lowered to room temperature in the argon atmosphere, and the negative electrode material is obtained after being dispersed, sieved and demagnetized. The mass of nano silicon particles and nitrogen-doped silicon particles accounts for 40wt% of the total mass of the negative electrode material.

[0083] Since the present comparative example 1 directly uses porous carbon as a matrix, and nitrogen is not doped in advance into the porous carbon matrix to form CN bonds, after the subsequent deposition of step (2) which is the same as that of example 1, the mass proportion of nano silicon particles and nitrogen-doped silicon particles in the negative electrode material of comparative example 1 is less than that of example 1 and comparative example 1. This indicates that the CN bonds formed between the carbon element and the nitrogen element in the nitrogen-containing porous carbon matrix in step (1) are beneficial to the subsequent deposition of silicon.

[0084] Example 4

[0085] The preparation process of the nitrogen-doped porous silicon-carbon negative electrode material in this embodiment is basically the same as that in Example 1, with the only difference being that the insulation time in step (2) is 4 hours, and the final increment of nano-silicon particles and nitrogen-doped silicon particles accounts for 50 wt% of the total mass of the nitrogen-doped porous silicon-carbon negative electrode material.

[0086] Example 5

[0087] The preparation process of the nitrogen-doped porous silicon-carbon negative electrode material in this embodiment is basically the same as that in Example 1, with the only difference being that the insulation time in step (2) is 5 hours, and the final increment of nano-silicon particles and nitrogen-doped silicon particles accounts for 54 wt% of the total mass of the nitrogen-doped porous silicon-carbon negative electrode material.

[0088] In order to better illustrate the effects of the embodiments of the present invention, comparative examples 3-4 are compared with the above embodiments 4-5.

[0089] Comparative Example 3

[0090] The negative electrode material preparation process of this comparative example is basically the same as that of Example 4, except that the insulation time in step (2) is 2 hours, and the final mass percentage of the nano silicon particles and nitrogen-doped silicon particles to the total mass of the negative electrode material is 43 wt%.

[0091] Comparative Example 4

[0092] The negative electrode material preparation process of this comparative example is basically the same as that of Example 4, except that the insulation time in step (2) is 6 hours, and the final increment of nano silicon particles and nitrogen-doped silicon particles accounts for 63 wt% of the total mass of the negative electrode material.

[0093] Example 6

[0094] The preparation process of the nitrogen-doped porous silicon-carbon negative electrode material in this embodiment is basically the same as that in Example 1, with the only difference being that the volume flow ratio of monosilane to ammonia in step (2) is 5:1, and the final increment of nano-silicon particles and nitrogen-doped silicon particles accounts for 49 wt% of the total mass of the nitrogen-doped porous silicon-carbon negative electrode material.

[0095] Example 7

[0096] The preparation process of the nitrogen-doped porous silicon-carbon negative electrode material in this embodiment is basically the same as that in Example 1, with the only difference being that the volume flow ratio of monosilane to ammonia in step (2) is 6:1, and the final increment of nano-silicon particles and nitrogen-doped silicon particles accounts for 52 wt% of the total mass of the nitrogen-doped porous silicon-carbon negative electrode material.

[0097] In order to better illustrate the effects of the embodiments of the present invention, comparative examples 5-6 are compared with the above embodiments 6-7.

[0098] Comparative Example 5

[0099] The negative electrode material preparation process of this comparative example is basically the same as that of Example 6, except that the volume flow ratio of monosilane to ammonia in step (2) is 10:1, and the mass of nano-silicon particles and nitrogen-doped silicon particles accounts for 52 wt% of the total mass of the negative electrode material.

[0100] Comparative Example 6

[0101] The negative electrode material preparation process of this comparative example is basically the same as that of Example 6, except that the volume ratio of monosilane to ammonia in step (2) is 1:1, and the final mass of nano-silicon particles and nitrogen-doped silicon particles accounts for 41 wt% of the total mass of the negative electrode material.

[0102] The silicon content and nitrogen content of the materials prepared in Examples 1-7 and Comparative Examples 1-6 of the present invention were tested. The testing methods are as follows. The test data are detailed in Table 1.

[0103] The silicon content is tested by the burning method, which is as follows: in an oxygen or air environment, the silicon-carbon material is burned at a high temperature of 1000°C, the carbon reacts with oxygen to generate CO2 gas and is discharged, the nitrogen element is converted into N2 gas and is discharged, the silicon reacts with oxygen to generate SiO2, and the material is finally converted into SiO2. According to the mass of the reaction product SiO2, the silicon content in the original sample can be calculated.

[0104] The nitrogen content is detected using a nitrogen, oxygen and hydrogen analyzer. The sample is first burned in a high-temperature furnace, usually in an environment above 1000°C. This process will convert the nitrogen in the sample into nitrogen gas. The gas produced by the combustion is separated into nitrogen and other gases through a cooling and separation device. The separated nitrogen is analyzed by a thermal conductivity detector (TCD). The signal output by the detector is analyzed by a data processing system, and the nitrogen content in the sample is finally calculated.

[0105] The materials prepared in the above-mentioned Examples 1-7 and Comparative Examples 1-6 were used to prepare negative electrode sheets: the nitrogen-doped porous silicon-carbon negative electrode materials in Examples 1-7 and the negative electrode materials in Comparative Examples 1-6 were respectively mixed with Super P conductive agent, sodium carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 16:2:1:1 to prepare aqueous negative electrode slurry, the solid content of the slurry was controlled at about 45wt%, and the slurry was mixed evenly using a homogenizer. The slurry was coated on copper foil with a coating thickness of 70μm, and the electrode sheet was obtained after drying at 80℃, rolling, cutting, and vacuum drying at 110℃ for 12 hours.

[0106] Assembling half-cells: Using the pole pieces prepared as described above, with metal lithium sheets as counter electrodes and reference electrodes, with CR2025 matching battery shells, Celgard2500 separators and 1 mol / L LiPF6 / ethylene carbonate + dimethyl carbonate (v / v=1:1) electrolyte (5.0 vol% fluoroethylene carbonate and 1.0 vol% ethylene carbonate were added) to complete the assembly of half-cells in a glove box. Six half-cells were assembled in each embodiment and comparative example, and the average values ​​of the first-cycle coulombic efficiency, charge specific capacity, cycle capacity retention rate after 100 cycles, and cycle capacity retention rate after 300 cycles were tested.

[0107] The assembled half-cell was tested: the six batteries respectively assembled in each embodiment and comparative example were simultaneously subjected to constant current cycle charge and discharge test on the Xinwei test system, the test voltage range was 0.01-2V, the test was carried out at room temperature, first discharged to 0.5V at 0.1C (1C=2000mAh / g), then discharged to 0.1V at 0.05C, discharged to 0.01V at 0.02C, and allowed to stand for 10 minutes; then charged to 1.5V at 0.1C, allowed to stand for 10 minutes, and the charge and discharge capacities after the first cycle were recorded respectively, and the first cycle coulomb efficiency was calculated; after 100 cycles in the above manner, the charge specific capacity was recorded, and the capacity retention rate after 100 cycles was calculated; after 300 cycles in the above test method, the capacity retention rate after 300 cycles was calculated, and the test results are shown in Table 1 below. The charge and discharge curve of the battery of Example 1 is as follows, Figure 2 As shown; the cycle curve of the battery of Example 1 after 100 cycles, as shown Figure 3 shown.

[0108] Table 1

[0109]

[0110] By comparing Examples 1-3 with Comparative Examples 1-2 in Table 1, it can be seen that the first-cycle charging specific capacity, first-cycle coulombic efficiency and capacity retention rate after 300 cycles of Examples 1-3 are all better than those of Comparative Examples 1-2. This is because when Example 1-3 prepares the nitrogen-containing porous carbon matrix in step (1), the CN bond formed by the carbon element and the nitrogen element is beneficial to the deposition of silicon in the subsequent step (2), while the nitrogen content in the nitrogen-containing porous carbon matrix in step (1) of Comparative Example 1 is only 0.5%, and Comparative Example 2 uses a porous carbon matrix without nitrogen doping. That is, when Example 1-3 prepares the nitrogen-containing porous carbon matrix in step (1), it has more CN bonds, which is more conducive to silicon deposition, thereby improving the capacity, rate performance and cycle performance of the battery.

[0111] By comparing Example 4-5 with Comparative Example 3-4 in Table 1, it can be seen that the first cycle charging specific capacity and the capacity retention rate after 300 cycles of Example 4-5 are better than those of Comparative Example 3. This is because the insulation time in step (2) of Comparative Example 3 is shorter than that of Example 4-5, so the mass of nano-silicon particles and nitrogen-doped silicon particles deposited in the pores of the nitrogen-containing porous carbon matrix of Comparative Example 3 accounts for a smaller proportion; the first cycle coulomb efficiency and the capacity retention rate after 300 cycles of Example 4-5 are better than those of Comparative Example 4, and Comparative Example 4 has a higher charging capacity. This is because the insulation time in step (2) of Comparative Example 4 is longer than that of Example 4-5, so the mass of nano-silicon particles and nitrogen-doped silicon particles deposited in the pores of the nitrogen-containing porous carbon matrix of Comparative Example 3 accounts for a larger proportion. Comparative Example 4 has a larger charging capacity, but due to the larger proportion of nano-silicon particles, the volume expansion problem of nano-silicon particles increases with the increase in the number of cycles. Therefore, the cycle performance of the battery of Comparative Example 4 is inferior to that of Example 4-5.

[0112] By comparing Examples 6-7 with Comparative Examples 5-6 in Table 1, it can be seen that the first-cycle charging specific capacity, first-cycle coulomb efficiency and capacity retention rate after 300 cycles of Examples 6-7 are better than those of Comparative Examples 5-6. This is because in step (2) of Comparative Example 5-6, the volume flow ratios of monosilane and ammonia are 10:1 and 1:1 respectively. The proportion of silicon source gas directly determines the total amount of deposited nano-silicon particles. Under the same deposition time, the higher the proportion of silicon source gas, the higher the silicon content in the final silicon-carbon composite material, the higher the specific capacity of the material, and thus the better the performance of the battery.

[0113] A method for preparing a nitrogen-doped porous silicon-carbon negative electrode material is provided in an embodiment of the present invention. The method comprises the following steps: nitrogen-doping porous carbon under a protective atmosphere to obtain a nitrogen-containing porous carbon matrix having a CN bond, and then depositing nano-silicon particles and nitrogen-doped silicon particles in the pores of the nitrogen-containing porous carbon matrix through chemical vapor deposition of a mixed gas of a nitrogen source and a silicon source to obtain a nitrogen-doped porous silicon-carbon negative electrode material.

[0114] The nitrogen-doped porous silicon-carbon negative electrode material obtained by the above-mentioned preparation method in the embodiment of the present invention is beneficial to improving the effective deposition of silicon and improving the utilization rate of silicon source gas due to the presence of CN bonds in the process of preparing the nitrogen-containing porous carbon matrix, thereby improving the performance of the nitrogen-doped porous silicon-carbon negative electrode material, so that it has the characteristics of high capacity, low expansion rate, high first-cycle coulomb efficiency, long cycle life and high rate performance.

[0115] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a nitrogen-doped porous silicon-carbon negative electrode material, characterized in that: The preparation method comprises: Step S1, placing porous carbon in a reaction furnace under a protective atmosphere, heating it to a first temperature, introducing a first nitrogen source gas, and cooling it to room temperature after a first heat preservation process, so as to obtain a nitrogen-containing porous carbon matrix doped with nitrogen in the pores of the porous carbon; wherein the carbon element of the nitrogen-containing porous carbon matrix forms a CN bond with the nitrogen element; and the mass percentage of the nitrogen element in the nitrogen-containing porous carbon matrix to the mass percentage of the nitrogen-containing porous carbon matrix is ​​2% to 10%; Step S2, under a protective atmosphere, placing a nitrogen-containing porous carbon matrix in a reaction furnace, heating it to a second temperature, introducing a second nitrogen source gas and a silicon source gas, and undergoing a second heat preservation process, wherein the CN bond induces the deposition of the silicon source gas so that nano-silicon particles and nitrogen-doped silicon particles are uniformly deposited in the pores of the nitrogen-containing porous carbon matrix, and after cooling to room temperature, breaking up, screening and demagnetizing, a nitrogen-doped porous silicon-carbon negative electrode material is obtained; the flow ratio of the silicon source gas to the second nitrogen source gas is between 3:1 and 8:

1.

2. The preparation method according to claim 1, characterized in that: The particle size Dv50 of the porous carbon is 5nm to 8nm; the pore size of the porous carbon is 1.5nm to 2nm; the porosity of the porous carbon is 50% to 70%; The mass ratio of the nano silicon particles to the nitrogen-doped silicon particles is 95%:5% to 90%:10%.

3. The preparation method according to claim 1, characterized in that: The protective atmosphere is an argon atmosphere; The first nitrogen source gas includes: one or more of ammonia and nitrogen oxides; the flow rate of the first nitrogen source gas is 12L / min to 16L / min; The second nitrogen source gas includes: one or more of ammonia and nitrogen oxides; the flow rate of the second nitrogen source gas is 12L / min to 16L / min; The silicon source gas includes one or more of monosilane, disilane, dichlorosilane, trichlorosilane, tetrachlorosilane and hexachlorodisilane.

4. The preparation method according to claim 1, characterized in that: The step S1 of heating the temperature to the first temperature includes: heating the temperature to 500°C to 700°C at a heating rate of 1°C / min to 5°C / min; The first heat preservation process includes: heat preservation at 500° C. to 700° C. for 1 hour to 5 hours.

5. The preparation method according to claim 1, characterized in that: The rotation speed of the reaction furnace in step S2 is 80 rpm to 100 rpm; The heating to the second temperature includes: heating to 500°C to 700°C at a heating rate of 1°C / min to 5°C / min; The second heat preservation process includes: heat preservation at 500° C. to 700° C. for 1 hour to 5 hours.

6. The preparation method according to claim 1, characterized in that: The dispersing device is a disperser; the speed of the disperser is between 80r / min and 1500r / min, and the dispersing time is 0.5 hours to 2 hours; The mesh size for sieving is between 200 and 500 mesh.

7. A nitrogen-doped porous silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The nitrogen-doped porous silicon-carbon negative electrode material comprises a nitrogen-containing porous carbon matrix, and nano silicon particles and nitrogen-doped silicon particles deposited in the pores of the nitrogen-containing porous carbon matrix.

8. The nitrogen-doped porous silicon-carbon negative electrode material according to claim 7, characterized in that: The mass ratio of the nano silicon particles to the nitrogen-doped silicon particles is 95%:5% to 90%:10%; The mass of the nano-silicon particles accounts for 40% to 52% of the total mass of the nitrogen-doped porous silicon-carbon negative electrode material; The particle size range Dv50 of the nitrogen-doped porous silicon-carbon negative electrode material is 5nm to 8nm.

9. A negative electrode plate, characterized in that: The negative electrode plate comprises the nitrogen-doped porous silicon-carbon negative electrode material as described in any one of claims 7-8.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode plate as described in claim 9 above; the lithium-ion battery comprises a liquid lithium-ion battery, a semi-solid lithium-ion battery or an all-solid lithium-ion battery.

Citation Information

Patent Citations

  • Porous silicon-carbon lithium ion battery anode material with high rate capability and preparation method thereof

    CN110600719A

  • Negative electrode material and preparation method thereof, electrochemical device and electronic device

    CN114051663A

  • Silicon-carbon negative electrode material, preparation method thereof and lithium ion battery

    CN116799178A

  • Negative electrode material and preparation method thereof, electrochemical device and electronic device

    CN118630167A